Bella’s Stereotyped Role through Stephenie Meyer’s Twilight - Abir, KHELIFI (My University, 2017)
This dissertation examines the restoration of the patriarchal system, along with woman’s oppression and psychological repression through Twilight, a story written by the American novelist, Stephenie Meyer. This scrutiny is significant in the fact that it brings to the surface patriarchal oppression of a protagonist inscribed in the world of vampirism. Throughout the story and from feminist and psychoanalytical point of view, the protagonist Bella Swan is apparently restricted to a feminine role, including her appearance, her thoughts, and her behaviours with males. Then, she is exposed to the consequences of the classical gender role. She is physically, economically, and psychologically oppressed. Therefore, this examination aims to analyse the character of Bella and show the disparity between her and her lover, Edward Cullen. Moreover, this research intends to exhibit the negative impacts of patriarchy, regarding the Otherness and the psychological oppression of Bella, individually and socially. To achieve these goals, this study called for two theories: the feminist standpoint of Simone de Beauvoir’s the Second Sex which helps identifying Bella’s gender alienation in a male dominated society. In addition to the Freudian psychoanalytical perspective that studies the function of Bella’s psyche, as well as her traumatic psychology which is induced by her inferior status. After investigation, it has been revealed that Bella is inhibited by her stereotypical female role. She is physically and psychologically oppressed. In other words, she is subjugated in a patriarchal world
Keywords: other words, she is subjugated in a patriarchal world.